Suku Bunga Kredit, Inflasi, dan Kredit Macet Pada Lembaga Perkreditan Desa - Berliana, Indah; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 33 No 10 (2023)DO - 10.24843/EJA.2023.v33.i10.p12, 2023)
Information related to the financial statements of a financial institution is closely related to the detailed amount of credit disbursed, including the value of bad credit as seen from the NPL value. This research aims to obtain empirical evidence of the influence of credit interest rates and inflation on Bad Credit/NPL in Village Credit Institutions (LPD) throughout Badung Regency during the period January 2018 to June 2021. This research uses multiple linear regression analysis techniques. The results of this research show that credit interest rates and inflation have a positive influence on non-performing loans/NPLs. For a financial institution, the higher the credit interest rate offered will result in an increase in the NPL value because the interest burden that must be paid by debtors relatively increases. Likewise, inflation can lead to an increase in overall prices and a weakening of the value of the rupiah, this of course makes it difficult for people to pay their credit installments and leads to LPD credit problems in the form of increasing non-performing loans/NPLs. Keywords: non-performing loan; credit interest rate; inflation